An observational study of headaches in children and adolescents with functional abdominal pain: Relationship to mucosal inflammation and gastrointestinal and somatic symptoms. Issue 30 (July 2018) - Friesen, Craig; Singh, Meenal; Singh, Vivekanand; Schurman, Jennifer V.
Abstract : Abstract: Headaches and abdominal pain are among the most common pediatric pain conditions. Mast cells have been implicated in the pathophysiology of migraines, as well as functional dyspepsia (FD) and irritable bowel syndrome (IBS). The primary aims of the current study were to assess headache prevalence in patients with FD and to assess the association between headaches and mucosal mast cells and eosinophils. An additional aim was to explore associations of headache with other symptoms. We conducted a cross-sectional retrospective chart review of 235 consecutive patients with chronic abdominal pain. All patients had completed a standardized questionnaire as part of their routine clinical evaluation. Both gastrointestinal and non-gastrointestinal somatic symptoms were included in the analysis. All patients diagnosed with FD had undergone upper endoscopy with biopsies obtained from the gastric antrum and duodenum and these specimens were utilized to assess eosinophil and mast cell densities, respectively. Overall, 86% of patients fulfilled Rome IV criteria for FD. Headache was reported by 73.8% of FD patients versus 45.2% of non-FD patients ( P = .001). Duodenal mast cell densities were significantly increased in those reporting headaches. Headache was not associated with any specific gastrointestinal symptoms but was associated with a wide array of non-gastrointestinal symptoms including fatigue, dizziness, muscle pain, joint pain, and chest pain. Headaches are common in children and adolescents with abdominal pain and, utilizing Rome IV criteria, are specifically associated with FD. In patients with FD, headaches are associated with increased duodenal mast cell density and a variety of somatic symptoms, all of which are possibly the result of mast cell activation.